ChemInform Abstract: 1, 3‐Dipolar Cycloadditions of Nitrile Oxides with 7‐Oxa‐ and 7‐Azabenzonorbornadienes. Issue 51 (23rd December 2014) - Nagireddy, Jaipal R.; Carlson, Emily; Tam, William
Abstract 1, 3‐Dipolar cycloadditions of 7‐oxa‐ and 7‐azabenzonorbornadienes with in situ generated nitrile oxides afford exclusively exo‐cycloadducts.